PERBANDINGAN SISTEM HUKUM INDONESIA DAN RUSIA TENTANG TINDAK PIDANA PENGHINAAN KEPALA NEGARA - Erlangga, Muhamat Ridwan; Gultom, Elfrida Ratnawati (Ensiklopedia of Journal, 2024)
The crime of insulting the head of state is one of the criminal acts regulated by legal systems in various countries, including Indonesia and Russia. This research aims to compare the legal arrangements and enforcement related to the crime of insulting the head of state in both countries. Through a normative approach with library research methods, this study analyzes laws and regulations, court decisions, and relevant literature from both countries. The results of the study show that there are significant differences in the legal arrangements and enforcement related to insulting the head of state in Indonesia and Russia. Indonesia has a specific law that regulates the criminal act of insulting the president and vice president, while Russia regulates it in a more general law concerning insulting public officials. Additionally, there are differences in the criteria and limitations of insults that can be criminalized, as well as the legal penalties that can be imposed. This research provides in-depth insights into the different legal approaches between Indonesia and Russia in regulating and enforcing the crime of insulting the head of state. These findings can be considered for legal reforms and improved law enforcement in both countries regarding this sensitive issue.Keywords: Insulting Head of State, Indonesian, Russian Legal System